Russian Non-Bolshevik Diplomacy and the Issue of International Recognition of the White Movement in 1918-1920 - E. M. Mironova (Vestnik MGIMO-Universiteta)
Gaining international recognition for the White Movement was the most important foreign policy task of the Russian non–Bolshevik diplomacy. The article traces the evolving discourse of career diplomats considering this issue at different stages of the civil war. It shows their deep patriotism, professionalism, and persistency in carrying out the task. However, when the allies did not share the slogans of the White Movement, the possibilities for finding common ground were very limited. At the first stage (summer-autumn 1918), diplomats were cautious about the claims for recognition of numerous Russian non–Bolshevik governments. In the second stage (1918 – 1919), the issue of recognition played a unique role – participation of Russian representatives in the peace conference, and therefore in determining the configuration of the post-war world, depended on its success. The resolve of the diplomats to defend the Russia’s national interests did not suit foreign powers, who did not share the movement's slogan about restoring a united and indivisible Russia, its power, and its position in the world. At the third stage (spring-summer 1920), diplomats, loosing hope for military victory of the White Movement in the civil war, withdrew from the direct involvement in seeking international recognition for the Movement. However, they provided all possible technical support to the head of the Department of External Relations of the Wrangel Government, Peter B. Struve, who assumed this mission. France's recognition of the Sevastopol authorities in the summer of 1920 was limited, did not involve active military assistance, and caused justified skepticism in diplomatic circles.